Overexpression of the endothelial protein C receptor is detrimental during pneumonia-derived gram-negative sepsis (Melioidosis) - Kager, L; Schouten, M; Wiersinga, W; Boer, D; Lattenist, L; Roelofs, J; Meijers, J; Levi, M; Dondorp, A; Esmon, C; Van 'T Veer, C; Van Der Poll, T (Public Library of Science, 2013)
Background The endothelial protein C receptor (EPCR) enhances anticoagulation by accelerating activation of protein C to activated protein C (APC) and mediates anti-inflammatory effects by facilitating APC-mediated signaling via protease activated receptor-1. We studied the role of EPCR in the host response during pneumonia-derived sepsis instigated by Burkholderia (B.) pseudomallei, the causative agent of melioidosis, a common form of community-acquired Gram-negative (pneumo)sepsis in South-East Asia. Methodology/Principal Findings Soluble EPCR was measured in plasma of patients with septic culture-proven melioidosis and healthy controls. Experimental melioidosis was induced by intranasal inoculation of B. pseudomallei in wild-type (WT) mice and mice with either EPCR-overexpression (Tie2-EPCR) or EPCR-deficiency (EPCR−/−). Mice were sacrificed after 24, 48 or 72 hours. Organs and plasma were harvested to measure colony forming units, cellular influxes, cytokine levels and coagulation parameters. Plasma EPCR-levels were higher in melioidosis patients than in healthy controls and associated with an increased mortality. Tie2-EPCR mice demonstrated enhanced bacterial growth and dissemination to distant organs during experimental melioidosis, accompanied by increased lung damage, neutrophil influx and cytokine production, and attenuated coagulation activation. EPCR−/− mice had an unremarkable response to B. pseudomallei infection as compared to WT mice, except for a difference in coagulation activation in plasma. Conclusion/Significance Increased EPCR-levels correlate with accelerated mortality in patients with melioidosis. In mice, transgenic overexpression of EPCR aggravates outcome during Gram-negative pneumonia-derived sepsis caused by B. pseudomallei, while endogenous EPCR does not impact on the host response. These results add to a better understanding of the regulation of coagulation during severe (pneumo)sepsis.